Subversión del sujeto: Althusser, Lacan, Badiou - Farrán, Roque (Nómadas. Critical Journal of Social and Juridical Science, 2009)
In this text I propose to make explicit the “subversion of the subject” that is deduced of the reading of materialistic and critical authors as Althusser, Lacan, Lévi-Strauss and Badiou; centring especially on the reading that Althusser de Marx does in Pour lire le capital.
Keywords: Subject; Subversion; Materialism; Psychoanalysis